Developments in Magnetic Pulse Welding - Pereira, Diogo Jorge de Oliveira Andrade (2021)
Magnetic Pulse Welding is a solid state joining technology based on impact, which allows to produce overlap joints both in planar and tubular geometries. The technology has seen an increased interest in recent years, especially as a result of the industrial need to joint dissimilar materials (metallic and non-metallic) which easily form brittle intermetallic phases when welded by fusion-based processes. However, no significant improvements on existing equipments have been reported, which are normally sized for endurance, compromising the machine efficiency. In fact these are normally equipped with large storage capacitors banks, which are sometimes insufficient for dissimilar material combinations that require more energy to weld In this study existing equipments were analysed to understand the key components aiming at its optimization. A prototype machine was developed and assembled envisaging higher discharge energies efficiency. The equipment was tested and validated in tubular transitions due to the facility to produce the coils in laboratory facilities but also due to the industrial applications identified. This joining process is known to need a conductive flyer material to allow inducing current for the magnetic interaction which projects the flyer against the target to produce a weld. Thus, tube to tube and tube to rod welds were produced in AA6063 in similar and dissimilar metallic joints to Ti6A4V. AA7075 to carbon fibre reinforced polymer tubes transitions were also successfully produced especially when Cu or Ni ductile interlayers were used. The developed prototype equipment was compared to a commercial machine to identify the optimization achieved and to compare characteristics of the welds produced. For this, the joints were characterized both structural and mechanically. The prototype machine proved to have a higher efficiency needing less than 15% of the energy required on the commercial machine to produce similar aluminium transitions (reducing from 16 kJ to 2 kJ). The machine also proved to be efficient in producing dissimilar joints, such as aluminium to titanium transitions and metal to non-metal transitions.